Manejo de ametropía en paciente con glaucoma primario de ángulo abierto controlado. - Fray Figueroa, Adriana Lissette (2020)
Refractive errors or ametropia are all those situations in which, due to optical malfunction, the eye is not able to provide a good image. To classify a reduction in visual acuity as ametropia or refractive disorder, it must be capable of being corrected by optical means. These disorders include myopia, hyperopia and astigmatism. As glaucoma is one of the main causes of blindness worldwide, the analysis of a patient with this disease is considered the same one that puts the loss of vision at risk in an irreversible way. Therefore, primary glaucoma is pathology of important psychosocial and economic connotation, the fear produced by losing the sense of vision is invaluable. This paper presents the case of a 67-year-old patient who reports decreased visual acuity due to uncorrected ametropia and a history of primary open-angle glaucoma, which is initially treated at the first level of health. In the ophthalmological control, he was recommended to carry out an annual check-up to follow up on said pathology and be able to apply all the correct medication to prevent the progression of said disease and not cause blindness, and with the optometric consultation his optical correction was prescribed, guiding us of the progress of said pathology, so that you can have an excellent visual quality both from far and near.